Strategy for Developing Superior Human Resources through Talent Management in Government Agencies in Support of the National Strategic Agenda - Jufri Halim (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the implementation of talent management in developing superior human resources in government agencies and its contribution to supporting the national strategic agenda. The study used a qualitative approach with a case study design, involving in-depth interviews, observation, and document analysis as data sources. The results show that talent management is implemented through systematic talent identification, development, and placement. The implementation of this strategy contributes to increased competency, leadership capacity, motivation, and employee retention. Supporting factors include government policies, committed leadership, organizational culture, and integrated HR information systems, while inhibiting factors include budget constraints, cultural resistance, and limited HRD capacity. This study recommends strengthening talent management through alignment with the national strategy, developing information systems, increasing the capacity of leaders and HRD, developing sustainable talent programs, and conducting regular monitoring and evaluation. These findings confirm that talent management is an effective strategic instrument in developing superior human resources and supporting the achievement of the national strategic agenda.